2017
DOI: 10.1038/cdd.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Rictor/mTORC2 deficiency enhances keratinocyte stress tolerance via mitohormesis

Abstract: How metabolic pathways required for epidermal tissue growth and remodeling influence the ability of keratinocytes to survive stressful conditions is still largely unknown. The mechanistic target of rapamycin complex 2 (mTORC2) regulates growth and metabolism of several tissues, but its functions in epidermal cells are poorly defined. Rictor is an adaptor protein essential for mTORC2 activity. To explore the roles of mTORC2 in the epidermis, we have conditionally deleted rictor in mice via K14-Cre-mediated homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
2
20
1
Order By: Relevance
“…sFLG also cuts glutamine levels and induces a double impact in cell homeostasis. Firstly, a reduction in glutamine levels could also be indicative of an enhanced consumption of the amino acid – a consequence of an adaptative response to mitochondrial stress 67 . Secondly, glutamine and glutamate, which is also diminished, are key metabolites for the synthesis of GSH 66 .…”
Section: Discussionmentioning
confidence: 99%
“…sFLG also cuts glutamine levels and induces a double impact in cell homeostasis. Firstly, a reduction in glutamine levels could also be indicative of an enhanced consumption of the amino acid – a consequence of an adaptative response to mitochondrial stress 67 . Secondly, glutamine and glutamate, which is also diminished, are key metabolites for the synthesis of GSH 66 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in glioblastoma cells, mTORC2 deficiency enhances the ability of cancer cells to adapt to unfavorable environmental conditions [ 7 ]. Moreover, mTORC2-deficient epithelial cells are significantly more resistant to oxidative stress [ 129 ]. Therefore, it is tempting to speculate that mTORC2/AKT upstream agonists may synergize with xCT inhibition and APR-246 in the eradication of tumor cells.…”
Section: Additional Potential Targets For Combined Therapiesmentioning
confidence: 99%
“…There issome evidence that redox mechanisms are related to the beneficial properties of LF, IF and CR, in the same way that exercise seems to be related to redox mechanisms [ 25 , 26 ]. The G-to-K switch leads to an increased number of mitochondria (mitohormesis) in order to accelerate aerobic catabolism of fats through the mechanisms of AMPK and SIRT [ 27 , 28 , 29 ]. Semi-quantitative metabolomic analysis in human whole-blood plasma and red blood cells during 34–58 h fasting in four subjects showed that 44 of ~130 metabolites increased rapidly, including antioxidant molecules.…”
Section: Introductionmentioning
confidence: 99%